2017
DOI: 10.1002/2016wr019997
|View full text |Cite
|
Sign up to set email alerts
|

The complexities of urban flood response: Flood frequency analyses for the Charlotte metropolitan region

Abstract: We examine urban flood response through data‐driven analyses for a diverse sample of “small” watersheds (basin scale ranging from 7.0 to 111.1 km2) in the Charlotte Metropolitan region. These watersheds have experienced extensive urbanization and suburban development since the 1960s. The objective of this study is to develop a broad characterization of land surface and hydrometeorological controls of urban flood hydrology. Our analyses are based on peaks‐over‐threshold flood data developed from USGS streamflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 117 publications
(164 reference statements)
5
61
0
Order By: Relevance
“…The largest overlap in storm events, 69 %, is found for the two largest basins, 48.5 and 111.1 km 2 in size. This confirms results reported by Smith et al (2013b) and Zhou et al (2017), who also found markedly different rainfall climatologies for flood-producing storms in basins of different size.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The largest overlap in storm events, 69 %, is found for the two largest basins, 48.5 and 111.1 km 2 in size. This confirms results reported by Smith et al (2013b) and Zhou et al (2017), who also found markedly different rainfall climatologies for flood-producing storms in basins of different size.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, spatial variability changes over the duration of events, more strongly so for the larger than for the smaller basins. This is a characteristic of hydroclimatic conditions in this region northeast of the Appalachians, as confirmed for instance by Zhou et al (2017). Similar results were found by Lobligeois et al (2014), who analyzed spatial variability of storm events associated with the largest 20 flood events in 181 basins in France.…”
Section: Spatial Rainfall Variability and Fractional Basin Coveragesupporting
confidence: 71%
See 3 more Smart Citations